Analysis of C-shaped root canal configuration in maxillary molars in a Korean population using cone-beam computed tomography - Hyoung-Hoon Jo; Jeong-Bum Min; Ho-Keel Hwang (Korean Academy of Conservative Dentistry, 2016)
Objectives The purpose of this study was to investigate the incidence of root fusion and C-shaped root canals in maxillary molars, and to classify the types of C-shaped canal by analyzing cone-beam computed tomography (CBCT) in a Korean population. Materials and Methods Digitized CBCT images from 911 subjects were obtained in Chosun University Dental Hospital between February 2010 and July 2012 for orthodontic treatment. Among them, a total of selected 3,553 data of maxillary molars were analyzed retrospectively. Tomography sections in the axial, coronal, and sagittal planes were displayed by PiViewstar and Rapidia MPR software (Infinitt Co.). The incidence and types of root fusion and C-shaped root canals were evaluated and the incidence between the first and the second molar was compared using Chi-square test. Results Root fusion was present in 3.2% of the first molars and 19.5% of the second molars, and fusion of mesiobuccal and palatal root was dominant. C-shaped root canals were present in 0.8% of the first molars and 2.7% of the second molars. The frequency of root fusion and C-shaped canal was significantly higher in the second molar than the first molar (p < 0.001). Conclusions In a Korean population, maxillary molars showed total 11.3% of root fusion and 1.8% of C-shaped root canals. Furthermore, root fusion and C-shaped root canals were seen more frequently in the maxillary second molars.